Correlation between Sociodemographic Variables and OncoE6 Cervical Swab Test Positive Cases - Nahar, Faijun; Hossain, Md Akram; Paul, Shyamal Kumar; Khatun, Sufia; Bhuiyan, Golam Rahman; Nasreen, Syeda Anjuman; Ahmed, Salma; Haque, Nazia (Community Based Medical Journal, 2022)
A cross-sectional, observational study was conducted to determine the relationship between sociodemographic variables and the development of cervical cancer through detection of detection of HPVE6 oncoprotein. A total of 47 endocervical swabs were collected from colposcopy clinic under the Department of Obstetrics & Gynaecology, Mymensingh Medical College, Mymensingh, Bangladesh, from January to December of 2015. Laboratory work was done in the Department of Microbiology of the same institution. E6 strip test is an immunochromatographic test based on detection of HPV-E6 oncoprotein in cervical swab samples. The swab specimen was treated with lysis solution and conditioning solution. Then the specimen solution was clarified by centrifugation. After that the sample solution was transferred into the detector mAb vial, wash solution vial, and finally, into developing solution vial. The test unit was then placed on a reading guide. Positive result was indicated by the appearance of purple colored test line. Out of 47 specimens, 21 (44.68%) were OncoE6 positive. Among those 21 positive cases, 19 (90.48%) were HPV-16 and 2 were (9.52%) HPV-18. Out of 11 histologically diagnosed CIN I cases, 1 (9.09%) case came out as positive. However, there were no positive cases by oncoE6 cervical swab test in CIN II and CINIII categories. Among histopathologically confirmed 22 cervical carcinoma cases, 20 (90.90%) came out as positive through this test. The results were compared with sociodemographic variables. OncoE6 is more common among ≥50 age group, and who got married before 18 years, and in multiparous women (P<0.05). Cervical cancer prevention services should be strengthen including health education, OncoE6 screening, and Anti-HPV vaccination. CBMJ 2022 July: vol. 11 no. 02 P: 152-157